Resolution of Family Conflicts in Fiction: A Comparative Study of TV Series from China and the United States - Sergio Pérez Torres (International Journal of Business and Social Science Research, 2024)
The main objective of this research paper is to conduct a comparative cross-cultural analysis of family conflicts in two distinct cultural contexts, as represented in television fiction from China and the United States. The author focuses on conflicts arising within families and portrayed in television series in both countries. To achieve this, a systematic and objective content analysis method is employed, examining family conflict situations presented in the narratives of these television productions. The results indicate that, for the most part, conflicts are resolved positively, reflecting the typical trend in television fiction to seek a happy ending, especially in commercial series. However, cultural variabilities are also observed in the paths each region has taken to reach these conclusions.